Outcomes following general anaesthesia in children with hypertrophic cardiomyopathy. Issue 5 (16th May 2019) - Norrish, Gabrielle; Forshaw, Natalie; Woo, Colleen; Avanis, Mary Claire; Field, Ella; Cervi, Elena; Iguchi, Akane; Kaski, Juan Pablo
Abstract : Background: Children with hypertrophic cardiomyopathy (HCM) have historically been considered to be high-risk candidates for general anaesthesia (GA), but there is currently a paucity of evidence regarding the safety of anaesthesia and perioperative outcomes in this population. Methods: Clinical features and outcomes of all paediatric patients (<18 years) with HCM undergoing GA between 2000 and 2016 were reviewed. Results: 86 patients (median 12.4 years (IQR 6.5, 14.9)) underwent 164 separate GA procedures. Aetiology included non-syndromic disease (n=44, 56%), malformation syndromes (n=22, 26%), inborn error of metabolism (n=10, 12%) and neuromuscular disease (n=4, 5%). At the time of GA, mean maximal wall thickness (MWT) on echocardiography was 19 mm (SD±8 mm), 23 (14%) patients had severe left ventricular hypertrophy (MWT>30 mm) and 35 (21%) patients had a haemodynamically significant left ventricular outflow tract (LVOT) gradient (>50 mm Hg). The majority (n=143, 87%) had no perioperative complications. 20 (12%) patients had minor perioperative complications: bradycardia (n=4), hypotension (n=15) or transient ST segment changes (n=1). One (0.6% of GA procedures) patient experienced a cardiac arrest during anaesthetic induction with death occurring 3 days later. Clinical parameters (including age, MWT, LVOT gradient, systolic and diastolic dysfunction) were not associated with an increased risk of complications Conclusions: This is the largest published series to date of paediatric patients with HCM undergoing GA, which demonstrates that, in an expert centre, patients can be anaesthetised with a relatively low perianaesthetic mortality (0.6%) and prevalence of minor complications (12%). Future studies are required to systematically identify clinical features that may predict anaesthetic risk.